Analysis of Social Work Practice Research Trends in the Post-Covid-19 Pandemic Era: A Bibliometric Study - Oman Sukmana; Juli Astutik; Hutri Agustino; Erinda Dwimagistri Sukmana (PT ARRUS Intelektual Indonesia, 2026)
The study aims to examine issues and focus research related to post-COVID-19 pandemic social work practices using bibliometric analysis. Data was collected from the Scopus database with the keywords